Peran Guru dalam Membentuk Nilai Religius Anak di Kelas IV SDIT Ash-Shiddiiqi Kota Jambi - Kaspun Nazir; Rhesti Laila Ulfa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe in depth the role of teachers in shaping the religious values of grade IV students at the Ash-Shiddiiqi Integrated Islamic Elementary School (SDIT) Jambi City. Religious values are an important part of the formation of children's character from an early age, especially in the Islamic-based school environment. This study uses a qualitative descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that teachers play a major role in the formation of religious values through example, habituation, integration of religious values in learning, and cooperation with parents. The formation of religious values is not only carried out in the classroom, but also through school activities with Islamic nuances such as congregational prayers, memorization of the Qur'an, and daily prayers. The success of religious character formation is greatly influenced by the consistency of teachers and support from the school and family environment.